IMPACTS OF TEACHING ON THE ANXIETY LEVEL OF PATIENTS HAVE UNDERGONE CORONARY ARTERY BYPASS GRAFT IN NEMAZEE HOSPITAL IN SHIRAZ - Navvabi, E; Derakhshan, A; Sharif, F; Amirghofran, A; Tabatabaei, H (Iran University of Medical Sciences, 2003)
Background: Coronary obstructive heart diseases have a great incidence in the world and Coronary Artery Bypass Graft (CABG) Surgery is one of the most effective treatments for these disorders. CABG is a crisis and a threat for patient and his family which produces a great deal of anxiety. Anxiety can produce mental, physiological and behavioral disorders. Researches indicated that pre- admission education can decrease the anxiety level and stress of the patient and his family. Nurse as a member of this health care team is responsible for this teaching. Objective: To assess the impact of teaching on the anxiety level of patients have undergone Coronary Artery Bypass Graft surgery. Design: This was an-experimental study and informations were obtained through Hamilton questionnaire. Sample: 60 subjects with required criterias were selected randomly and divided into experimental (30) and control (30) groups. Result: findings showed that in the experimental group, the mean of anxiety level was 22 in the first stage and 6.4 in the second stage which had a statistically significant relationship (p=0/0001) while in the control group, the mean of anxiety level was 18.6 in the first stage and 28.3 in the second stage which was not found significantly related (p=0/134). Conclusion: A significant difference was found between the experimental and control groups from the Point of their anxiety level. (p= 0/0001) showing the positive effect of teaching on reducing the anxiety level in patients have undergone Coronary Artery Bypass Graft Surgery